Design and implementation of observability system based on event storage engine - CHEN Hongxi; QIU Xiaobin; QU Yang; CAO Lei; WANG Juzheng; CHEN Xin (Tongxin xuebao)
To solve the challenges posed by the significant increase in software system complexity due to the drastic changes in software architecture and the widespread adoption of new technologies over the past decade—challenges that have led to a surge in software bugs and difficulties in system failure troubleshooting, a design and implementation method for a more flexible and efficient monitoring system tailored to traditional monolithic service-based monitoring systems was proposed. The method abstracted traditional monitoring data sources into a unified event model and designed a corresponding storage engine that offered a unified query and write API. Based on the event storage engine, an observability system was constructed, providing richer and more powerful querying and analysis capabilities. The final application results demonstrate that, compared to traditional monitoring systems, the observability system developed in this paper significantly enhances efficiency in troubleshooting and problem analysis.